Photophysical Properties of Novel Phthalocyanines: Multi Emission by Excited at Short Wavelength - ZHAO, PENG; PARK, YONG-SUNG; WOO*, JE-WAN (Asian Journal of Chemistry, 2024)
Two novel phthalocyanines: tetra-azobenzene substituted zincphthalocyanine ZnPc.(Oazo)4 and polymeric ytterbium phthalocyaninecarboxyl (YbPPc.COOH) have been synthesized and their electronicadsorption and emission spectra have been investigated by spectrometricmethod. Both of the synthesized compounds can emit two fluorescentpeaks when excited at short wavelength (below 400 nm) and one peakwhen excited at long wavelength (higher than 600 nm) as well. ForYbPPc.COOH, in pH 7.4 buffer solution, when excited at 330 nm, besidenormal fluorescent peak at 720 nm, a second emission peak appeared at455 nm. The fluorescence quantum yield of two emission was 0.35(720 nm em, 635 nm ex) and 0.33 (455 nm em, 330 nm ex), respectively.This equivalent multi-emission phenomenon by different excited wavelengthindicates good applied potential in photodynamic diagnose andfluorescence imagination.